Lack of plakoglobin leads to lethal congenital epidermolysis bullosa: a novel clinico-genetic entity - Pigors, Manuela; Kiritsi, Dimitra; Krümpelmann, Sebastian; Wagner, Nicola; He, Yinghong; Podda, Maurizio; Kohlhase, Jürgen; Haußer-Siller, Ingrid; Bruckner-Tuderman, Leena; Has, Cristina (Human molecular genetics, 2011)
Epidermal integrity is essential for skin functions. It is maintained by adhesive structures between keratinocytes, mainly the desmosomes and adherens junctions, which provide resistance against mechanical stress and regulate the formation of the skin barrier. As a constituent of both types of intercellular junctions, plakoglobin has multiple interaction partners and mutations in its gene [junction plakoglobin (JUP)] have been associated with mild cutaneous disease, palmoplantar keratoderma and arrhythmogenic heart disease. Here we report a novel lethal phenotype caused by a homozygous nonsense JUP mutation, c.1615C>T, p.Q539X, which is very different from any human or murine JUP phenotype described so far. The patient suffered from severe congenital skin fragility with generalized epidermolysis and massive transcutaneous fluid loss, but apparently no cardiac dysfunction. In contrast to previously reported JUP mutations where truncated proteins were still present, in this case there was complete loss of plakoglobin in the patient's skin, as demonstrated by immunofluorescence and immunoblot analysis. As a consequence, only very few abnormal desmosomes were formed and no adhesion structures between keratinocytes were recognizable. The expression and distribution of desmosomal components was severely affected, suggesting an essential role for plakoglobin in desmosomal assembly. Adherens junction proteins were localized to keratinocyte plasma membrane, but did not provide proper cell-cell adhesion. This lethal congenital epidermolysis bullosa highlights the fundamental role of plakoglobin in epidermal cohesion.